PENINGKATAN KEMAMPUAN MEMBACA MELALUI TEKNIK PERMAINAN MENYUSUN KATA PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 1 SD INPRES CAMBAYA 1 KOTA MAKASSAR (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to improve the reading ability of first grade students at SD Inpres Cambaya 1 through word-composing game techniques in learning Indonesian. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in 3 meetings. The research procedure consists of planning, implementing actions, observing and reflecting. The subjects in this study were 28 class I students of SD Inpres Cambaya I, Makassar City. The research instruments used were observation sheets (students and teachers), interview text sheets, evaluation test sheets. Data collection techniques in this study were observation, interviews, evaluation and documentation. The collected data were then analyzed using qualitative and quantitative analysis.The results showed that in the first cycle students' reading ability increased by 53% or 15 students out of 28 students who met the minimum completeness criteria (KKM). Meanwhile, in cycle II students' reading ability increased by 82% or 23 students out of 28 students who met the completeness criteria (KKM). Thus the results of the study can be concluded that, using the word-composing game technique can improve the reading ability of class I SD Inpres Cambaya I Makassar City in learning Indonesian.